The Concept of Homeliness-in-Care in Nurse Emotional Labor in Pediatric and Community End-of-Life Settings. - Eryl Maunder (Asia-Pacific Journal of Oncology Nursing, 2013)
Place matters. The context of where care is provided impacts on the emotional labour of nurses. Nurses providing palliative care for children and young people living with life limiting, life threatening and end of life care needs were influenced by their place of work. The children's hospices were designed around places of 'home from home' and the nurses responded by portraying that they felt at home in their work. the community children's nurses worked to ensure their visits into the homes where not seen as an intrusion for families. They portrayed an image of 'being at home' in the homes of others so that those receiving care felt more relaxed with their input into their homes.Maunder, E.Z. (2015):